Electrochemical Impedance Spectroscopy Based Biosensors: Mechanistic Principles, Analytical Examples and Challenges towards Commercialization for Assays of Protein Cancer Biomarkers. Issue 4 (21st September 2018) - Bertok, Tomas; Lorencova, Lenka; Chocholova, Erika; Jane, Eduard; Vikartovska, Alica; Kasak, Peter; Tkac, Jan
Abstract: Impedimetric affinity biosensors are, without any doubt, among the most sensitive analytical devices available, offering low limits of detection and wide linear response ranges. There are, however, only a few papers detailing the application of impedimetric biosensors for the analysis of clinically relevant samples with due clinical performance. The fact that these devices have not found their way to any commercial or clinical use to date might be surprising, since an electrochemical assay platform based on portable potentiostats is a success story for monitoring a range of clinical parameters such as ions, haematological indicators and glucose. This review discusses the reasons behind this discrepancy and addresses the barriers to be overcome in order to achieve the point‐of‐care diagnostics using such devices for detection of protein oncomarkers approved by FDA. The final part of the review covers the most recent progress in the area. Abstract : Impedimetric biosensors : The review article provides mechanistic principles behind electrochemical impedance spectroscopy with discussion about the limitation of the detection principle. The final part of the review highlights analytical examples for detection of several tumor biomarkers with analytical characteristics of such biosensors provided.